Altered glycosylation of exported proteins, including surface immune receptors, compromises calcium and downstream signaling responses to microbe-associated molecular patterns in Arabidopsis thaliana. Issue 1 (December 2016) - Trempel, Fabian; Kajiura, Hiroyuki; Ranf, Stefanie; Grimmer, Julia; Westphal, Lore; Zipfel, Cyril; Scheel, Dierk; Fujiyama, Kazuhito; Lee, Justin
Abstract Background Calcium, as a second messenger, transduces extracellular signals into cellular reactions. A rise in cytosolic calcium concentration is one of the first plant responses after exposure to microbe-associated molecular patterns (MAMPs). We reported previously the isolation ofArabidopsis thaliana mutants with a "changed calcium elevation " (cce ) response to flg22, a 22-amino-acid MAMP derived from bacterial flagellin. Results Here, we characterized thecce2 mutant and its weaker allelic mutant, cce3 . Besides flg22, the mutants respond with a reduced calcium elevation to several other MAMPs and a plant endogenous peptide that is proteolytically processed from pre-pro-proteins during wounding. Downstream defense-related events such flg22-induced mitogen-activated protein kinase activation, accumulation of reactive oxygen species and growth arrest are also attenuated incce2/cce3 . By genetic mapping, next-generation sequencing and allelism assay, CCE2/CCE3 was identified to beALG3 (Asparagine-linked glycosylation 3 ). This encodes the α-1, 3-mannosyltransferase responsible for the first step of core oligosaccharide Glc3 Man9 GlcNAc2 glycan assembly on the endoplasmic reticulum (ER) luminal side. Complementation assays and glycan analysis in yeastalg3 mutant confirmed the reduced enzymatic function of the proteins encoded by thecce2/cce3 alleles – leading to accumulation of M5ER, the immature five mannose-containing oligosaccharide structure found in the ER. Proper protein glycosylation is required for ER/Golgi processing and trafficking of membrane proteins to the plasma membrane. Endoglycosidase H-insensitivity of flg22 receptor, FLS2, in thecce2/cce3 mutants suggests altered glycan structures in the receptor. Conclusion Proper glycosylation of MAMP receptors (or other exported proteins) is required for optimal responses to MAMPs and is important for immune signaling of host plants.